Pregnancy in a Transgender Male: A Case Report and Review of the Literature. (29th June 2022) - Hassan, Ayesha; Perini, Jessica; Khan, Amna; Iyer, Apoorva
Abstract : Introduction . Pregnancy in transgender men is an area of increasing study due to data showing that pregnancy can occur in this population despite the reduction in fertility that generally accompanies treatment with gender-affirming hormone therapies. Case . In this case, we describe a healthy 21-year-old transgender man who was able to achieve pregnancy without reproductive assistance after stopping his testosterone therapy for 2 months. Discussion . Our case is important as it highlights how little is known in regards to gender-affirming hormone therapy on fertility. While testosterone is known to reduce fertility by inducing anovulation and altering ovarian histology, its long-term effects on conception rates and pregnancy are largely unknown. Some studies demonstrate that transgender men, treated with gender-affirming hormone therapy (GAHT), including testosterone, have similar oocyte quantity and quality, as well as similar ovarian reserve, when compared to cisgender women, suggesting that resumption of fertility may be possible after cessation of GAHT. Long-term outcomes for the pregnancy and the offspring of those who have been treated with GAHT are unknown. Conclusion . Recent studies have shown that pregnancy is possible for transgender men who desire biological children and have received gender-affirming hormonal therapy without fertility-preserving measures. Further research is needed to help determine rates of fertility, the likelihood of recovery of fertility, conception rates, and long-term pregnancy outcomes. Such information would help guide physicians in providing education and counseling to their transgender patients regarding reproductive options.